Розвиток фтизіатрічної допомоги в Запоріжжі (до 105-річчя протитуберкульозної служби області) - Просвєтов, Юрій Васильович; Ахтирський, О. І.; Растворов, Олександр Анатолійович; Тищенко, О. В.; Скороходова, Наталя Олегівна; Гусарова, Аліна Юріївна; Растворова, О. О.; Prosvеtov, Yu. V.; Akhtirskiy, O. І.; Rastvorov, O. A.; Tishchenko, O. V.; Skorokhodova, N. O.; et al. (Запорізька медична академія післядипломної освіти, 2018)
Боротьба з сухотами в Запоріжжі розпочалась на початку ХХ сторіччя. Першим протитуберкульозним закладом був створений у 1904 р. за ініціативою земства санаторій у Бердянську. В Олександрівську у 1911 р. заснована філія Всеросійської ліги боротьби з туберкульозом, яка відкрила у 1913 р. амбулаторію з лабораторією та аптекою. Новий етап фтизіатричної допомоги розпочався на початку 20-х років, коли були відкриті диспансери в Бердянську, Запоріжжі, Мелітополі, перша в Україні сільська протитуберкульозна лікарня. Проведення заходів боротьби з туберкульозом призвело до покращення епідеміологічної ситуації. Проте, під час війни служба була зруйнована, її відродження відбулось у 1943 р. Мережа закладів фтизіатричної служби поступово охоплювала всі міста та райони області. Вперше в Україні в області були застосовані бронхологічні дослідження (1956), визначення чутливості МБТ до препаратів (1957), організовані денні стаціонари для лікування хворих (1986), створено обласне «Спеціалізоване територіальне медичне об’єднання «Фтизіатрія» (1993), розпочато впровадження виявлення захворювання в загальних лікувальних закладах методом мікроскопії мокротиння (1999). Фтизіатрична служба з 2003 р. співпрацює з ВООЗ, РАТН, Глобальним фондом для боротьби зі СНІДом, туберкульозом та малярією. В області вперше в Україні була розроблена та впроваджена програма соціальної підтримки хворих на туберкульоз. Це єдиний регіон країни, де відкриті кабінети психологічної та соціальної допомоги пацієнтам на вперше діагностований туберкульоз чи коінфекцію ТБ/ВІЛ. The fight against tuberculosis in Zaporizhzhia has been carried out from the beginning of the XX century. The first anti-tuberculosis institution was the sanatorium created in 1904 on the initiative of the countyin Berdyansk. In 1911 in Aleksandrovsk, a branch of the All-Russian League for the Fight against Tuberculosis was founded and an outpatient clinic with laboratory and pharmacy was opened in 1913. A new stage of phthysiatric care started in the early 1920s, when dispensaries in Berdyansk, Zaporozhzhia, Melitopol and the first village tuberculosis hospital were opened. The implementation of the measures to combat tuberculosis has led to an improvement of the epidemiological situation. However, during the war the TB service was destroyed, its revival took place in 1943. The network of phthisiatric agencies gradually covered all the cities and districts of the region. The regional dispensary became the clinical base of the phthisiatric departments of the Institute for Advanced Training of Physicians and the Medical Institute, which allowed to introduce new methods of detection and treatment of the disease. Zaporizhia region became the first one in Ukraine where bronchial studies were applied (1956), the sensitivity of the MBT to drugs was determined (1957), day hospitals for the treatment of patients were organized (1986), the regional “Specialized territorial medical association «Phthysiology» was established (1993), the detection of disease in general medical institutions by the method of sputum microscopy was introduced (1999). Since 2003, the TB Service has been cooperating with WHO, PATH, the Global Fund to Fight AIDS, Tuberculosis and Malaria. The diagnostic capabilities of the service are constantly improved – fibrobronchoscopy, ultrasound diagnosis, automated system BACTEC MGIT 960, polymerase chain reaction on the analyzer Xpert MTB/RIF are applied. Program of social support for tuberculosis patients was developed and implemented which is the first time in Ukraine. Zaporizhzhia region is the only region in Ukraine where psychological and social care offices for patients with newly diagnosed tuberculosis or coinfection with TB/HIV are opened. TB Service of the Zaporizhia region has been continuously working for 105 years to reduce and overcome this disease in the region.
Development of phthisiatric care in Zaporozhzhye (for the 105-th anniversary of the Tuberculosis Service of Region)
Keywords: фтизіатрична служба; історичний розвиток; Запорізька область; phthysiological service; historical development; Zaporizhzhia region